CITRAAN TOKOH UTAMA PEREMPUAN PADA KUMPULAN CERPEN MEREKA BILANG SAYA MONYET KARYA DJENAR MAESA AYU (KAJIAN FEMINISME RADIKAL) - Z, Silfiana (Fakultas Bahasa dan Sastra Indoensia, 2020)
aimed at describing images and efforts to liberate the main female characters against patriarchs. This research is descriptive qualitative with reading and note taking techniques, then identifying, classifying, interpreting, and describing based on the novel. Radical feminism, a collection of short stories, illustrates the radical movement for women, which has been carried out to undermine the prevailing norms. Provide understanding of the violence of sexuality harassment to gender inequality between women and patriarchy.